The The Effect of Intellectual Capital on Financial Performance with Financial Distress as A Moderation Variable - Kartikasari, Devanti; Yudiana, Fetria Eka (Jurnal Magister Ekonomi Syariah, 2023)
Increasing the performance company is the objective main for the company For attract investors. Financial performance can be used by management to make decisions. Financial performance information is very important for investors as a tool for choosing investments. The company's financial performance shows its ability to use the existing resources of the company as well as possible in order to generate profit or income. The objective of the study is To know the influence of intellectual capital, sales growth, and leverage on performance finances, and know is financial distress can moderate the relationship between independent and dependent variables. Population in study This is a company registered manufactures _ in the Indonesian Sharia Stock Index (ISSI) and obtained a sample of as many as 20 companies. Study This using multiple linear regression techniques and Moderating Regression Analysis (MRA) with application eviews. Research results This shows that influential intellectual capital has a positive significance on performance finance, sales growth No influence on performance finance, leverage significant negative effect on performance finance, financial distress capable moderate influence on intellectual capital to performance finance, financial distress No capable moderate influence sales growth to performance finance, financial distress No capable moderate influence leverage to performance finance.